Analysis of Pre-service History Teachers’ Attitudes Toward the Use of Distance Education Environments - Alaca, Eray; Agbal, Sema (Journal of Education for Sustainability and Diversity, 2025)
The purpose of this study is to analyze attitudes of pre-service history teachers toward the use of distance education environments. It was examined whether attitudes of pre-service history teachers toward using distance education environments differed by gender, class, internet access, and device type. The research study group consisted of 86 pre-service history teachers studying in the History Department of the Faculty of Science and Literature at a Turkish state university. As data collection tools, the "Attitude Scale Regarding the Use of Distance Education Environments During the Pandemic Process" consisting of 25 items and the "Personal Information Form" consisting of 6 questions were applied to the participants. The data collected for the study was analyzed using the SPSS 24.0 program. As a result, it was found that pre-service history teacher attitudes toward using distance education environments were below intermediate.